The Apparent Lack of Emphasis in the Context of University Education - Thamilsellvan a/l Pamanathe; Sakinah Balqis Nor Azman; Nordini Emily Mohathir; Muhammad Ameerul Iman Shamsul Kamal; Yasin Ibrahim; Mohamad Aizi Selamat (Applied Information Technology And Computer Science, 2023)
This study investigates the challenges and opportunities in projectmanagement education within higher institutions, with a focus on key PMBOKdomains. It highlights the significance of ef ective communication in project successand the need to integrate soft skills within classroom settings alongside technicalknowledge in project management. It also emphasizes the significance of humanresource management in education, encouraging the involvement of students incurriculum development to enhance engagement and practical application oftheoretical knowledge. Quality management is seen as crucial for maintainingeducational consistency and relevance, while time and scope management ensurewell-targeted goals. The abstract suggests future research through a comparativeanalysis of dif erent educational approaches and the importance of collaborationsbetween educational institutions and industries to provide real-world experiences tostudents.